Effects of Body Weight of Semi-Heavy Cocks on Reproductive Indices and Yields of Incubation - Rufino, J.P.F.; Cruz , F.G.G.; Melo, R.D.; Feijo, J. da C.; Silva, R.O. da; Brandao, A.B.T.; Berenchtein, B. (International Journal of Poultry Science, 2015)
The study aimed to evaluate the reproductive traits in poultry breeder with different weight ranges of two semi-heavy lineages. The experimental method was completely randomized design in factorial arrangement (3 x 2) with two factors: reproductive methods (artificial insemination and natural mating) and two semi-heavy strains (Plymouth Barred Rock and Rhode Island Red). All birds used in this experiment were subjected to identical conditions of nutritional management and breeding. Were evaluated the phenotypic characteristics of breeders andrological analysis of semen, performance of females inseminated and biometrics of chicks from males selected and ranked by lineages and weight ranges. The lineages evaluated showed significant differences how much your reproductive characteristics observed best results for lineage Rhode Island Red, where this shown highest efficiency of improving the productive and reproductive yields, can this has a tendency for relationship with the performance of the progeny. Cocks with 3 kg of body weight showed best body condition for semi-heavy breeding of both lineages, with superiority results for indices evaluated, featuring a direct influence between body weight and the reproductive rates of semi-heavy cocks.